Uso progresivo de la fuerza del servidor policial en un acto de servicio - Garzón, Mónica F. (2022)
The present investigation was chosen with the purpose of making known what are the limitations that the police server has to make progressive use of force in the fulfillment of its duty, considering that force may be used only in strictly necessary cases, that is to say when it is the last option, for which two aspects must be taken into consideration, the circumstance in which the event occurs and the criteria of the police officer who takes the procedure, however it was evidenced that the lack of training of the officials in charge of doing complying with the law, is a trigger when fulfilling their duty, not knowing how to act in situations of extreme danger, which implies inefficient work that threatens citizen security, putting them at a disadvantage compared to the antisocial, we can state that in the present investigation more general research methods were applied such as: inductiveanalytical method comparative method and case study method, the research technique used is the interviews through the application of a questionnaire with open questions, with all this it was established that the responsibility of the Ecuadorian State is the formation and training of the members of the the national police, for this it is necessary to create new public policies aimed at strengthening citizen security.